A sensitive fluorescence sensor for glutathione detection based on MnO2 nanosheets–copper nanoclusters composites. Issue 83 (22nd August 2016) - Wang, Hai-Bo; Chen, Ying; Li, Yang; Liu, Yan-Ming
Abstract : A sensitive fluorescence sensor has been developed for glutathione detection based on MnO2 nanosheets–Cu NCs composites. Abstract : In this paper, a novel fluorescent sensing strategy has been developed for sensitive detection of glutathione (GSH) on the basis of MnO2 nanosheets–copper nanoclusters (Cu NCs) composites. Highly fluorescent Cu NCs were synthesized using bovine serum albumin (BSA) as template through a facile one-step chemical reduction method. When MnO2 nanosheets–Cu NCs composites formed, the fluorescence intensity of the Cu NCs could be efficiently quenched by the MnO2 nanosheets. However, upon the addition of GSH, MnO2 could be reduced to Mn 2+ ions, leading to the inhibition of the MnO2 nanosheets induced fluorescence quenching effect. As a result, the fluorescence intensity of Cu NCs recovered. Under the optimal conditions, the developed sensor exhibited sensitive and selective detection for GSH in a linear range from 0 μM to 300 μM and with a detection limit of 100 nM. Importantly, the strategy possessed great selectivity toward GSH relative to other metal ions and amino acids. Furthermore, the method was successfully applied to determinate the GSH levels in human serum samples with satisfactory results. Besides, the proposed sensing system showed some advantages including simple, rapid detection, low cost and easy preparation.